The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1016/j.ajpath.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Endothelial Transforming Growth Factor–β Signaling Leads to Choroidal Neovascularization

Abstract: The molecular pathogenesis of choroidal neovascularization (CNV), an angiogenic process that critically contributes to vision loss in age-related macular degeneration, is unclear. Herein, we analyzed the role of transforming growth factor (TGF)-β signaling for CNV formation by generating a series of mutant mouse models with induced conditional deletion of TGF-β signaling in the entire eye, the retinal pigment epithelium (RPE), or the vascular endothelium. Deletion of TGF-β signaling in the eye caused CNV, irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 85 publications
(78 reference statements)
1
43
0
2
Order By: Relevance
“…This is in accordance with previous studies showing TGF-b1 upregulation in OIR. 60 Interestingly, conditional ocular deletions of TGF-b signaling results in pronounced structural changes of retinal capillaries and a phenotype similar to human DR. 61,62 The upstream regulator analysis identified Mkl2 and FIGURE 8. Selection of upregulated proteins at P42 OIR.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous studies showing TGF-b1 upregulation in OIR. 60 Interestingly, conditional ocular deletions of TGF-b signaling results in pronounced structural changes of retinal capillaries and a phenotype similar to human DR. 61,62 The upstream regulator analysis identified Mkl2 and FIGURE 8. Selection of upregulated proteins at P42 OIR.…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β plays a vital role in the formation and development of CNV by Smad2/3-VEGF/TNF-α signaling pathway in wet AMD [88]. Interestingly, other studies indicated that deficient of TGF-β signaling leads to retinal degeneration and exacerbates CNV [89,90]. Furthermore, TGF-β promotes the EMT of RPE cells, induces subretinal fibrosis and production of IL-6 [60].…”
Section: Cytokinesmentioning
confidence: 99%
“…Specularly, in the developing eyes of mice lacking Tgf-β2 (Tgfb2 −/− ), persistent vitreous vessels could be detected [ 50 ]. Moreover, the induced conditional deletion of TβRII in the entire eye or in the vascular endothelium of the eye, but not in RPE, caused an increased retinal expression of VEGF-A, the development of CNV, and the induction of other phenotypic characteristics of nAMD [ 71 ]. In a mouse model of oxygen-induced retinopathy, intraperitoneally injected human placental amniotic membrane-derived mesenchymal stem cells migrated into the retina and suppressed excessive neovascularization by TGF-β1 expression [ 72 ].…”
Section: Evidence For Antiangiogenic Function Of Tgf-β In Namdmentioning
confidence: 99%